2021
DOI: 10.1038/s41598-021-00020-3
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and low HDL cholesterol predict coronary heart disease risk in patients with stable angina

Abstract: We assessed whether high triglycerides (TG) and low high-density lipoprotein cholesterol (HDL-C) levels, expressed by an increased TG/HDL-C ratio, predict coronary atherosclerotic disease (CAD) outcomes in patients with stable angina. We studied 355 patients (60 ± 9 years, 211 males) with stable angina who underwent coronary computed tomography angiography (CTA), were managed clinically and followed for 4.5 ± 0.9 years. The primary composite outcome was all-cause mortality and non-fatal myocardial infarction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 39 publications
5
26
0
Order By: Relevance
“…It was suggested that the TG/HDL-C ratio could be used as an indicator of LDL subfraction [ 29 ]. In addition, TG/HDL-C ratio increases systemic and vascular inflammatory processes by decreasing endothelial protective mechanisms, which leads to progressive coronary atherosclerosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the TG/HDL-C ratio could be used as an indicator of LDL subfraction [ 29 ]. In addition, TG/HDL-C ratio increases systemic and vascular inflammatory processes by decreasing endothelial protective mechanisms, which leads to progressive coronary atherosclerosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a prospective, multicenter study enrolling 355 patients with stable angina at intermediate-low risk referred to coronary computed tomography angiography (CTA) and followed for 4.5 years, patients with a higher TG/HDL-C ratio presented a higher coronary atherosclerosis burden ( 21 ). In addition, both a higher TG/HDL-C ratio and the coronary CTA score were additional predictors of worse outcome, independently of other cardiovascular risk factors, the presence of obstructive CAD or ischemia ( 21 ). In contrast to these controlled studies, VHR CCS patients included in our registry were undertreated with statin therapies and were followed up for a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, the results of our analyses highlight the potentiality of measuring lipid species as new biomarkers of evolving atherosclerotic risk and to guide clinical management and target specific treatments in patients with CCS. In these patients, the identification of a specific condition of residual CAD risk not tackled by current treatments is a relevant clinical unmet need [12,44] and a potential target of new treatments [12,45].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in a European multicenter population of stable patients with CCS, highest TG/ HDL-C ratio highlights a specific lipid species signature able to identify patients with higher CAD risk. The research of new molecular pathways has a pivotal importance in the fight against residual risk, and in development of new targeted nutritional, lifestyle and drug strategies beyond the established LDL-C lowering interventions [12,45]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation